Tachydromia monacha Melander Holarctic 1928 - Shamshev, Igor V.; Grootaert, Patrick (Zenodo, 2024)
Tachydromia monacha Melander (Fig. 12) Tachydromia monacha Melander, 1928: 283. Type locality: USA, Washington, Pullman. Tachydromia monaca : Melander, 1965: 474; Yang et al. , 2007: 440. Error or emendation. Notes on type series. Melander (1928) described this species from female sex only: “ one specimen, Pullman, Washington, May 30, 1913 ”. Type material examined. HOLOTYPE ♀, labelled: Pullman, Washington, 30 May 13 [= 1913] // TYPE, T . monacha Mel. [red label, species name hand-written] // A.L. Melander Collection 1961 (USNM). Additional material examined: NORTH AMERICA. CANADA. Alberta: Morrin, 4.vi.1929, G.F. Manson (1 ♀, CNC); Valleyview, 6.vi.1961, A. R. Brooks (1 ♀, CNC). British Columbia: Summit Lake, mi. 392 Alaska Hwy, 4500’, 11–14.vii.1959, R. E. Leech (1 ♂, 3 ♀, CNC); same locality, 4700’, 15.vii.1959, R. E. Leech (1 ♂, 1 ♀, CNC); same locality, 4500’, 17–19.vii.1959, R.E. Leech (1 ♂, 5 ♀, CNC). Northwest Territories: Yellowknife, 1.vi.1953, J.G. Chillcott (1 ♀, CNC). Saskatchewan: Saskatoon, 27.v.1925, N.J. Atkinson (1 ♀, CNC); same locality, 17.v.1926, K.M. King (1 ♀, CNC); same locality, 25.v.1926, K.M. King (1 ♀, CNC); same locality, 3.vi.1926, K.M. King (2 ♂, 8 ♀, CNC); same locality, 21.vi.1926, K.M. King (1 ♀, CNC). Yukon: Ross River, 132°30′ 61°56′, 3000’, 21.vi.1960, J.E.H. Martin (2 ♂, CNC). USA. Alaska: Fairbanks, 14.vi.1952, W.R. Mason (1 ♀, CNC). California: Nevada Co., Prosser Creek @ Hwy 89, 39°23′50.2″N 120°11′13.9″W, 14.vii.2012, S.E. Brooks (1 ♀, CNC). EURASIA. RUSSIA. Altay Republic: 10 ♂, 14 ♀, Kosh-Agach distr., 20 km W Belir, Dzhelo River, 2100 m, 49°57′N, 87°52′E, 24–25.vi.2014, leg. I. Shamshev (10 ♂, 14 ♀, ZISP). Diagnosis. A small robust species (body 1.5–2 mm), distinguished by the following combination of characters: proepisternum tomentose; legs almost uniformly brown, only knees yellowish; wings faintly brownish in cells r 1 and r 2+3, halter with dark knob. Redescription. Male (described for first time, Fig. 12A). Length: body 1.6–1.8 mm, wing 1.6–1.7 mm. Head black. ...